Estimating the teaching contact hours based on fuzzy maps : new approach: al-Shaykh, Hasan al-Sarim, Muhammad - al-Shaykh, Hasan al-Sarim, Muhammad (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Current paper presents an innovative approach for developing a course specification taking in consideration the impact of the covered topics in a course on the whole program learning outcomes. It presents a practical methodology allowing instructors to design an efficient course specification based on the national academic accreditation and assessment standards